1998
DOI: 10.1523/jneurosci.18-18-07189.1998
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spreading Depression and Associated Intracellular Calcium Waves in Brain Slices

Abstract: Spreading depression (SD) was analyzed in hippocampal and neocortical brain slices by imaging intrinsic optical signals in combination with either simultaneous electrophysiological recordings or imaging of intracellular calcium dynamics. The goal was to determine the roles of intracellular calcium (Ca2+int) waves in the generation and propagation of SD. Imaging of intrinsic optical signals in the hippocampus showed that ouabain consistently induced SD, which characteristically started in the CA1 region, propag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(141 citation statements)
references
References 40 publications
14
127
0
Order By: Relevance
“…Astrocytes, the predominant type of glial cells in the central nervous system, form a highly organized multicellular syncytium extending throughout the gray matter (3,4). Calcium imaging in acute brain slices and in vivo has demonstrated that astrocytes can generate various patterns of activity, either local and spatially restricted to processes of individual cells or coordinated between adjacent cells and propagating across the brain tissue (5)(6)(7)(8)(9)(10)(11)(12). Modeling indicates that coupling of astrocytic and neuronal activities may give rise to membrane potential instability and oscillations (13).…”
mentioning
confidence: 99%
“…Astrocytes, the predominant type of glial cells in the central nervous system, form a highly organized multicellular syncytium extending throughout the gray matter (3,4). Calcium imaging in acute brain slices and in vivo has demonstrated that astrocytes can generate various patterns of activity, either local and spatially restricted to processes of individual cells or coordinated between adjacent cells and propagating across the brain tissue (5)(6)(7)(8)(9)(10)(11)(12). Modeling indicates that coupling of astrocytic and neuronal activities may give rise to membrane potential instability and oscillations (13).…”
mentioning
confidence: 99%
“…56). Thus Basarsky et al (2) showed that CSDs in calcium-free medium also occurred in the absence of intercellular calcium waves. In addition, metabolic poisons for astroglial cells, fluoroacetate and fluorocitrate, did not prevent CSDs but rather facilitated their onset (37).…”
Section: Interastroglial Communication and Csdsmentioning
confidence: 99%
“…Several forms of astrocytic calcium waves have been described under artificial or pathological conditions, such as in cultured astrocytes (Cornell-Bell et al, 1990;Charles et al, 1991;Finkbeiner, 1992) and in spreading depression (SD) (Basarsky et al, 1998;Kunkler and Kraig, 1998;Peters et al, 2003;Chuquet et al, 2007). Glissandi differ in several respects from these previously known waves.…”
Section: Glissandi As Novel Dynamicsmentioning
confidence: 99%